THE INTERACTION BETWEEN GLOBAL CLIMATE CHANGE AND TROPICAL FOREST ECOSYSTEMS - Rozak, Andes Hamuraby (LIPI Press, 2013)
In the last 100 years, the global mean temperature has increased approximately 0.6oC and is predicted to increase approximately 1.1oC to 6.4oC in the end of 21st century. On the other hand, deforestation still continues with the rate of -5.2 million hectares per year. This global climate change phenomenon in physical dimension has been analyzed in detail; yet its effect to the changes of biodiversity particularly in tropical forest ecosystems is still poorly understood. From the literature review, it is clear that there is correlation between global climate change and tropical forest ecosystems. The effect of climate change to forest ecosystems itself includes species range shifts, species extinction risks, biome shifts, and biogeochemical cycling. Furthermore, the deforestation of tropical forestecosystems also has reverse effects to the global climate change, i.e. is increasing the amount of green house gasses which directly changes the three climatic variables which are the Earth surface temperature, the total precipitation, and the atmospheric moisture convergence.